TOTALIZING SOVEREIGNTY: SECURITIZATION AND THE PARADOX OF STRONG STATE POWER IN PAPUA - Jonathan Christian (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2026)
This paper examines the paradox of Indonesia's approach to Papua. Decades of securitization and large-scale, state-led development—intended to ensure stability and integration—have instead deepened the conflict and created conditions of fragility they sought to eliminate. This argument is rooted in Indonesia's use of political securitization to defend its territorial integrity, has further heightened internal conflict and created new societal uncertainty. By synthesizing the logics of sovereignty, securitization theory, and strong-state theory, this paper introduces “totalization logic” to describe Jakarta’s approach, which limits space and imposes a top-down approach, despite the formal existence of autonomy mechanisms. Instead of being utilized as intended, this special autonomy law has been instrumentalized to centralize Indonesian policy and marginalize grassroots voices. Using qualitative methods, this study shows that the failed decentralization and Jakarta's central intervention have led to counterproductive outcomes and even produced international spillover effects, scrutinized by Melanesian regional bodies and United Nations human rights mechanisms and thus elevating what Jakarta treats as a domestic threat into international concern. The paper’s findings contribute to IR scholarship by showcasing securitization theory beyond the interstate realm, demonstrating how domestic political securitization logic generates insecurity rather than resolving it. The author also aims to show scholars and policymakers the limits of strong-state approaches to secessionist conflicts across Indonesia’s easternmost province and its relations to the transnational bond within the Melanesian region.